States Report Teaching, Research Activities - Maurice White (Journal of Applied Communications, 1978)
In 1978 the Ad Hoc Committee on Teaching and Research surveyed ACE members or information staffs at the Land-Grant institutions, including Puerto Rico, of the United States.